UNITED KINGDOM AND USA’S LEGISLATIONS TO CLEAN HISTORIC CONTAMINATION - Mr. Mahfud (Fakultas Hukum Universitas Gadjah Mada, 2013)
The industrial revolutionaries have left harmful residues on and in the land. Dealing with such contamination, the UK introduces Part 2A of the Environmental Protection Act (EPA) 1990 and the USA has legislated CERCLA 1980. This essay is going to discuss both provisions in cleaning up the contamination in each jurisdiction. We reach into a conclusion that both EPA 1990 and CERCLA 1980 govern the cost of cleaning up historic contamination, provide broad definition for the meaning of liable persons, and recognise the retroactivity principle. We find that there is a bifurcation of polluters classification in UK laws. This bifurcation is absent in US laws. Revolusi industri telah menyisakan bahan yang berbahaya baik di atas maupun di bawah permukaan tanah. Untuk mengatasi pencemaran bahan berbahaya tersebut, Inggris telah menerbitkan Bagian 2A EPA 1990 sementara Amerika Serikat telah mengesahkan CERCLA 1980. Tulisan ini mengkaji kedua aturan negara tersebut. Disimpulkan bahwa baik EPA 1990 maupun CERCLA 1980 sama-sama memiliki ketentuan yang mengatur perihal biaya pembersihan kontaminasi historis, mendefinisikan makna ‘orang yang bertanggungjawab’ secara luas, dan mengakui prinsip retroaktifitas. Hukum Inggris mengklasifikasikan pencemar, namun hukum Amerika Serikat tidak memiliki sistem klasifikasi tersebut.